Joint Association between Sedentary Time and Moderate-to-Vigorous Physical Activity with Obesity Risk in Adults from Latin America - de Victo, Eduardo Rossato; Fisberg, Mauro; Solé, Dirceu; Kovalskys, Irina; Gómez, Georgina; Rigotti, Attilio; Cortes, Lilia Yadira; Yépez-Garcia, Martha Cecilia; Pareja, Rossina; Herrera-Cuenca, Marianella; Drenowatz, Clemens; Christofaro, Diego [UNESP]; et al. (MDPI, 2023)
Recent studies have shown various relationships between physical activity and the incidence of obesity, but this study critically explored the association of sedentary time (ST) and moderate-to-vigorous physical activity (MVPA) with obesity risk in adults from eight Latin American countries. ST and MVPA were assessed with accelerometers and stratified into 16 joint categories. Multivariate logistic regression models were used. The obesity risk indicators evaluated were body mass index (BMI), waist circumference (WC), and neck circumference (NC). Quartile 4 of ST and ≥300 min/week of MVPA was associated with lower odds of BMI compared to quartile 1 of ST and ≥300 min/week of MVPA. Quartile 1 of ST and 150–299 min/week of MVPA, quartile 1 of ST and 76–149 min/week MVPA, quartile 3 of ST and 76–149 min/week MVPA, and quartiles 1, 2, and 3 of ST with 0–74 min/week MVPA were associated with higher odds of high WC compared to quartile 1 of ST and ≥300 min/week of MVPA. Quartile 3 of ST and 150–299 min/week of MVPA, quartiles 1 and 3 of ST and 76–149 min/week of MVPA, and quartile 1 of ST and 0–74 min/week MVPA were associated with higher NC compared to quartile 1 of ST and ≥300 min/week of MVPA. This study suggests that achieving the MVPA recommendations will likely protect against obesity, regardless of ST.
Keywords: obesity; physical activity; sedentary behavior; sitting time; South America